Microbial Test: Combination of Kefir Milk, Star Fruit, and Red Ginger - Wardani, Kartika Arum; Chamidah, Nurul (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
One of drinks with high nutritional value and good for health is milk kefir. The advantage of milk kefir compared to yogurt (another fermented beverage) they are richer withÂ probiotics. Goat's milk kefir contains more nutrients than cow's milk. To increase the production of sweet star fruit plants, the innovation of kefir milk drink combined with sweet star fruit juice and red ginger juice can be used as an alternative health drink that can increase body immunity. Each ingredient has the same benefits such as having antioxidant, antibacterial, anti-inflammatory, antiviral and immunomodulatory activities. In this study, researchers wanted to know the microbiological quality of the combination of milk kefir, sweet star fruit Juice and red ginger. The study was conducted from February to May 2021. Microbiological tests carried out were Methylene blue test, MPN test and total plate count test. The research design used a completely randomized design which focused on one factor, namely the concentration of red ginger extract (control concentration 0%, 4.5%, 6%, 7.5%). This experiment was used with replicas 3 times. The results showed that kefir fermented goat milk with the addition of sweet star fruit juice and ginger juice was good for consumption, namely in treatment group 1 (containing 20% â€‹â€‹star fruit juice and 4.5 percent red ginger juice).